2008
DOI: 10.1038/oby.2007.35
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Adiposity in Childhood: A Systematic Review of Cross‐sectional Studies 1990–2005

Abstract: background: Sobal and Stunkard's review (1989) of 34 studies from developed countries published after 1941, found inconsistent relationships between socioeconomic status (SES) and childhood adiposity. Inverse associations (36%), no associations (38%), and positive associations (26%) were found in similar proportions. In view of the trends in pediatric obesity, the relationship between SES and adiposity may have changed. objective: To describe the cross-sectional association between SES and adiposity in school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

89
655
13
35

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 772 publications
(792 citation statements)
references
References 60 publications
89
655
13
35
Order By: Relevance
“…As reported in the literature, the most important sociodemographic factor explaining children's obesity status is parental education level, which is consistently inversely associated with children's body weight and adiposity (5,11) . Our results are Table 3 Results from logistic regression analysis to evaluate the main effect of various socio-economic and demographic characteristics of parents on the likelihood of childhood overweight/obesity, stratified by gender: nationwide sample of primary-school children aged 10-12 years, GRECO (Greek Childhood Obesity) study, October-May 2009 reflective of such a relationship, suggesting that the level of education of the father is more likely to influence beliefs, knowledge on nutrition and health behaviours of the family, which in turn are involved in weight control through better nutritional and physical activity habits of the children (5,(12)(13)(14) . Although maternal education level did not seem to influence the odds for overweight/obesity, an interesting finding of our study was that maternal profession appeared to influence the likelihood of the child being overweight/ obese at the bivariate level.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As reported in the literature, the most important sociodemographic factor explaining children's obesity status is parental education level, which is consistently inversely associated with children's body weight and adiposity (5,11) . Our results are Table 3 Results from logistic regression analysis to evaluate the main effect of various socio-economic and demographic characteristics of parents on the likelihood of childhood overweight/obesity, stratified by gender: nationwide sample of primary-school children aged 10-12 years, GRECO (Greek Childhood Obesity) study, October-May 2009 reflective of such a relationship, suggesting that the level of education of the father is more likely to influence beliefs, knowledge on nutrition and health behaviours of the family, which in turn are involved in weight control through better nutritional and physical activity habits of the children (5,(12)(13)(14) . Although maternal education level did not seem to influence the odds for overweight/obesity, an interesting finding of our study was that maternal profession appeared to influence the likelihood of the child being overweight/ obese at the bivariate level.…”
Section: Discussionmentioning
confidence: 90%
“…Although obesity and particularly childhood obesity has a multifactorial nature, it has been shown that obesity status differs by social class and demographic factors (4,5) . However, a recent review by Shrewsbury and Wardle (5) highlighted the fact that the relationship between childhood overweight/obesity and socio-economic status (SES) depends on the SES indicator used and that, consequently, it is important to identify the correct sociodemographic influences on obesity status in contemporary societies in order to design and implement effective prevention initiatives. Early prevention is more effective in managing the epidemic of obesity, in comparison with treating obesity in later life.…”
mentioning
confidence: 99%
“…Negative associations between SEP and body weight in high-income countries have also been observed in childhood (20,21) . Moreover, during the next few decades inequalities in obesity are predicted to widen in some countries (22) .…”
Section: Current Evidence On Socio-economic Inequalities In Diet and mentioning
confidence: 94%
“…This pattern was not clearly visible in the paediatric population in the past (18) ; however it has become more apparent in the last 15 years (19) . In our study, the XXL family was characterized by a lower educational status of both parents, whereas the mother's tertiary education seemed to act as a protective factor against a family becoming overweight.…”
Section: Discussionmentioning
confidence: 91%